Effect of Human Resource Quality Of Economic Development In West Sumatra Province - Wasmani, Wasmani; Maryati, Sri; Yolamalinda, Yolamalinda (Pendidikan Ekonomi, 2014)
ABSTRACT The aims of this study to analyze the influence of Human Resources Quality which measured by the variable infant mortality, life expectancy and school enrollment rates towsed economic development in the province of West Sumatra. The research an inductive study, and used secondary data at years 1997-2011. Data were collected through library research, publications or data is recorded West Sumatra Biro.The tool analysis in this study is an econometric approach using multiple regression equation in the from a double log equation. The partial results showed that variable life expectancy and enrollment rates and a significant positive effect on Economic Development in the province of West Sumatra, while the infant mortality rate has no effect on economic development. The result of simultaneously significant all variable used in the study hive significant influance on Economic Development in West Sumatra province . Results of the study conclude that the Economic Development in West Sumatra province can be encouraged to improve the quality of human resources through the reduction of infant mortality rate, life expectancy and improving school participation rate in the province of West Sumatra .